KEPADATAN POPULASI BELALANG KEMBARA (Locusta migratoria L.) PADA TANAMAN JAGUNG DI KELURAHAN PISANG KECAMATAN PAUH PADANG - Oktaria, Rika; Jasmi, Jasmi; safitri, Elza (Pendidikan Biologi, 2014)
ABSTRACT One of the harmful insects in maize is the wanderer Grasshopper (Locusta migratoria L.). Grasshopper wanderer often found the area under maize cultivation . Grasshopper wanderer, both young (nymphs) and old, eating the leaves of corn plants, thereby reducing the surface area of leaves. Adult grasshoppers usually eat the leaf edges , while his nymph takes in between bones , causing leaves holes in the leaves. If this locust attack in a high number of population, the leaves of corn plants that are attacked will be devoured. In connection with the matter, has done research on  grasshopper  population  density  wanderer  on  corn  in  the  Village  Banana  Padang  Pauh subdistrict which aims to determine the wanderer grasshopper population densities on corn plants in Padang Pauh subdistrict Banana Village. This study was conducted in September-October 2013, with the method sweep (sweeping) is a way to swing a grasshopper inseknet existing wanderer on corn which is used as a place of research. Field sampling conducted on maize age of 1 month and2 months after planting by using inseknet and hands. Widely used as a research area of 20x20 m. Sampling was conducted at five points with a size of 3x3 m at each point. Physical environmental factors measured are temperature and humidity. From the research that has been conducted in the village of Padang Pauh subdistrict Bananas can be concluded that the grasshopper population density wanderer in maize of different ages 1 month to 2 months of age. Wanderer grasshopper populations on corn gained as much as 1 month of age 0.7 individuals/m² (0.3 nymphs and 0.4 imago), population density is lower than in maize aged 2 months gained as much as 1.8 individuals/m² (0,7 nymphs and 1.1 imago). Grasshopper population density wanderer found already included in the criteria pests.